Preattentive processing of emotional musical tones: a multidimensional scaling and ERP study - Münte, Thomas F.; Spreckelmeyer, Katja; Altenmüller, Eckart; Colonius, Hans (Frontiers in Psychology, 2013)
Musical emotion can be conveyed by subtle variations in timbre. Here, we investigated whether the brain is capable to discriminate tones differing in emotional expression by recording event-related potentials (ERPs) in an oddball paradigm under preattentive listening conditions. First, using multidimensional Fechnerian scaling, pairs of violin tones played with a happy or sad intonation were rated same or different by a group of non-musicians. Three happy and three sad tones were selected for the ERP experiment. The Fechnerian distances between tones within an emotion were in the same range as the distances between tones of different emotions. In two conditions, either 3 happy and 1 sad or 3 sad and 1 happy tone were presented in pseudo-random order. A mismatch negativity for the emotional deviant was observed, indicating that in spite of considerable perceptual differences between the three equiprobable tones of the standard emotion, a template was formed based on timbral cues against which the emotional deviant was compared. Based on Juslin’s assumption of redundant code usage, we propose that tones were grouped together, because they were identified as belonging to one emotional category based on different emotion-specific cues. These results indicate that the brain forms an emotional memory trace at a preattentive level and thus extends previous investigations in which emotional deviance was confounded with physical dissimilarity. Differences between sad and happy tones were observed which might be due to the fact that the happy emotion is mostly communicated by suprasegmental features.